INDUCTION OF SYSTEMIC RESISTANCE AGAINST BARLEY YELLOW DWARF VIRUS USING PSEUDOMONAS FLUORESCENS & AZOTOBACTER CHROOCOCCUM - & Jarjees, Abbas (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Pseudomonas fluorescens and Azotobacter chroococcum and mixture of bacteria are used to induce systemic resistance in barley variety (AL-Bowraq) against barley yellow dwarf virus. The result showed all treatments are effective to reduce the concentration of the virus compared with the control treatment (infested plant only). The most effective treatment was bacteria mixture as it was the highest reading for the value of the absorption at wavelength 405 nm 1.8 Compared with the control treatment, which is the highest reading for the value of the absorption 2.55 nm. This results come matching with the results of field experience as the treatment of bacteria mixture lead significantly to the rest of the treatments in all studies traits (number of spikes per plant, number of grains per spike, 1000 - grain weight and spike length). The highest rate of accumulation of phenols was when the seed treated with a mixture of bacteria compared with the other treatment and reached the highest rate of accumulation of phenols in the fourth day in the treatment of bacteria mixture compared with the control treatment which is reached the highest rate of accumulation of phenols in the tenth day. When measuring the effectiveness of the peroxidase enzyme the treatment of bacteria mixture recorded the highest rate of change in the absorption value compared with the control treatment, and the highest rate of change in the absorption value in the treatment of bacteria mixture was on the fourth day compared with the control treatment which gave the highest rate of change in the absorption value on the eighth day.